2003
DOI: 10.1152/ajpheart.00085.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and renal effects of low-dose brain natriuretic peptide infusion in humans: a randomized, placebo-controlled crossover study

Abstract: Brain natriuretic peptide (BNP) is a cardiac hormone with natriuretic activity. The aim of this study was to investigate the cardiovascular effects of pathophysiological levels of BNP on central hemodynamics, cardiac function, renal hemodynamics and function, and microvascular hemodynamics in healthy subjects. In this double-blind, placebo-controlled crossover study, we intravenously infused BNP (4 pmol. kg-1. min-1) or placebo for 1 h on two separate days in 12 healthy subjects (mean age, 60 +/- 5 yr). Nailfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
5
28
1
Order By: Relevance
“…The study participants remained lying down and fasted throughout the study, and exhibited, in agreement with 129±12 131±11 74±8 79±10 65±13 69±16 −30 125±10 129±6 75±8 76±3 66±13 64±11 0 129±14 129±7 77±7 77±6 66±12 65±11 30 125±14 131±10 74±5 76±8 64±13 65±10 60 127±8 125±11 73±7 74±11 61±9 70±12* 90 126±12 128±11 73±7 73±9 59±6 64±6 120 121±13 124±13 73±7 73±10 60±6 62±8 150 120±10 121±12 72±8 72±9 63±6 65±8 180 123±12 121±12 72±7 71±8 61±7 68±7* 270 121±9 128±21 71±6 74±7 60±6 73±15* previous findings, no significant changes in blood pressure [24]. Heart rate was significantly higher during BNP infusion compared with placebo at time points 60, 180 and 270 min (p<0.05) ( Table 2), which might be due to a non-significant decrease in blood pressure.…”
Section: Discussionsupporting
confidence: 74%
“…The study participants remained lying down and fasted throughout the study, and exhibited, in agreement with 129±12 131±11 74±8 79±10 65±13 69±16 −30 125±10 129±6 75±8 76±3 66±13 64±11 0 129±14 129±7 77±7 77±6 66±12 65±11 30 125±14 131±10 74±5 76±8 64±13 65±10 60 127±8 125±11 73±7 74±11 61±9 70±12* 90 126±12 128±11 73±7 73±9 59±6 64±6 120 121±13 124±13 73±7 73±10 60±6 62±8 150 120±10 121±12 72±8 72±9 63±6 65±8 180 123±12 121±12 72±7 71±8 61±7 68±7* 270 121±9 128±21 71±6 74±7 60±6 73±15* previous findings, no significant changes in blood pressure [24]. Heart rate was significantly higher during BNP infusion compared with placebo at time points 60, 180 and 270 min (p<0.05) ( Table 2), which might be due to a non-significant decrease in blood pressure.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, studies of BNP have come to conflicting conclusions about the effects on glomerular filtration rate (GFR) or renal plasma flow. [5][6][7] The extent of the renal effects of nesiritide when given in therapeutic doses to decompensated CHF patients is uncertain.…”
Section: See P 1514mentioning
confidence: 99%
“…5,15 Even these studies, however, have not necessarily demonstrated improved ERPF. 6 Nesiritide appears to exert hemodynamic effects in patients with both CHF and renal dysfunction (although the effects may be quantitatively different from those seen in normal individuals). 16 Clinically, CHF patients with an elevated creatinine concentration had a response similar to those with normal renal function in the Vasodilation in the Acute Management of CHF trial.…”
Section: Gfr and Erpfmentioning
confidence: 99%
See 1 more Smart Citation
“…Both compounds show natriuretic, diuretic, and vasodilating effects [17,18]. While there is good evidence of positive short-term hemodynamic effects of nesiritide in ADHF [19], there still is controversy regarding its safety risks, including renal dysfunction and long-term mortality [20], that needs to be addressed in future trials.…”
Section: Guanylate Cyclase Pathwaymentioning
confidence: 99%